The Judicial System with special reference to India - Dhadge, Anuradha; Deshpande, Bhagyashree (International Journal of Psychosocial Rehabilitation, 2020)
In a democratic system every organ of the state plays an important role and performs vital functions, however the judiciary has to perform a most crucial, difficult and major task as compared to the role played by the legislature and the executive. For the entire population of India there is one united judicial system. Sometimes it may happen that while performing the function these two organs i.e. executive and legislative may get politically motivated, while judiciary is usually neutral and unbiased and tries to uphold the rule of law acting as custodian, guardian or can say watchdog in safeguarding the citizens rights. The Judge is looked upon as a symbol of justice. People approach court for seeking justice and feel frustrated if justice is denied to them. Judiciary in India is not only competent to interpret the laws enacted by the Parliament but also to pronounce upon their validity. But in recent times it has been observed that judiciary is losing its creditability, trustworthiness, reliability in justice delivery system. There are number of cases found against judicial system doing corruption or immoral activity . This article lays down the jurisprudential theories on judiciary and rule of law and also appointment system and other drawbacks in present judicial system.